Static Formation Temperature Prediction Based on Bottom Hole Temperature - Changwei Liu; Kewen Li; Youguang Chen; Lin Jia; Dong Ma (Energies, 2016)
Static formation temperature (SFT) is required to determine the thermophysical properties and production parameters in geothermal and oil reservoirs. However, it is not easy to determine SFT by both experimental and physical methods. In this paper, a mathematical approach to predicting SFT, based on a new model describing the relationship between bottom hole temperature (BHT) and shut-in time, has been proposed. The unknown coefficients of the model were derived from the least squares fit by the particle swarm optimization (PSO) algorithm. Additionally, the ability to predict SFT using a few BHT data points (such as the first three, four, or five points of a data set) was evaluated. The accuracy of the proposed method to predict SFT was confirmed by a deviation percentage less than ±4% and a high regression coefficient R2 (>0.98). The proposed method could be used as a practical tool to predict SFT in both geothermal and oil wells.